2017
DOI: 10.1515/acph-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

A study on blocking store-operated Ca2+ entry in pulmonary arterial smooth muscle cells with xyloketals from marine fungi

Abstract: In this study, the effect of four xyloketals 1-4 on store-operated calcium entry (SOCE) was investigated in primary distal pulmonary arterial smooth muscle cells (PASMCs) isolated from mice. The results showed that xyloketal A (1), an unusual ketal with C-3 symmetry, exhibited strong SOCE blocking activity. Secretion of interleukin-8 (IL-8) was also inhibited by xyloketal A. The parallel artificial membrane permeability assay (PAMPA) of 1-4 suggested that these xyloketals penetrated easily through the cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As an important second messenger in cells, Ca 2+ is closely related to a series of important physiological and pathological processes, such as proliferation, differentiation, development, and cell death. The accumulated evidence has demonstrated that when cells are stimulated with T-2 toxin, it leads to the activation of store-operated calcium entry, which plays a crucial role in regulating Ca 2+ signaling and cellular responses in arterial smooth muscle cells [ 30 ]. Notably, Decuypere et al has reported that Ca 2+ is the key player in the canonical mTOR-controlled autophagy pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important second messenger in cells, Ca 2+ is closely related to a series of important physiological and pathological processes, such as proliferation, differentiation, development, and cell death. The accumulated evidence has demonstrated that when cells are stimulated with T-2 toxin, it leads to the activation of store-operated calcium entry, which plays a crucial role in regulating Ca 2+ signaling and cellular responses in arterial smooth muscle cells [ 30 ]. Notably, Decuypere et al has reported that Ca 2+ is the key player in the canonical mTOR-controlled autophagy pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, STIM1 is the "key" to activate calcium channels on the cell membrane. STIM1 is widespread in nonexcitable cells, including tumor cells and vascular smooth muscle cells (VSMCs) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%